The Effect of Malay Animation Series on Children’s Language Use in Sukamanah Village, Sukabumi Regency - Rieke Siti Gestiani; Supendi, Deden Ahmad; Firdaus, Asep (Aksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
This research aims to describe the effect of Malay animated series on the use of children's language. The data in this study contains the form of children's language use that is influenced by the spectacle of Malay animated series, such as Upin-Ipin, Boboiboy, and other Malay animations. So the effect of watching the Malay animated series caused interference in the use of children's language, namely Malay the Indonesian. This research uses a qualitative approach with a descriptive method. The type of research used is a case study. The data collection technique uses observation techniques, which are to review related children who often watch Malay animated series. Then using the documentation technique related to recording the speech carried out, recording the form of use of Malay into the Indonesian spoken by the child. Data analysis techniques use data reduction techniques, data presentation, and concluding. The source of this research data is children in Sukamanah Village, Sukabumi Regency. The results of this study show the form of language interference in the field of linguistics, namely phonology, morphology, and syntax. Abstrak Penelitian ini bertujuan untuk mendeskripsikan efek serial animasi Melayu terhadap penggunaan bahasa anak. Data dalam penelitian ini memuat tentang bentuk penggunaan bahasa anak yang dipengaruhi dari tontonan serial animasi Melayu, seperti Upin-Ipin, Boboiboy, dan animasi Melayu lainnya. Sehingga efek dari menonton serial animasi Melayu tersebut mengakibatkan interferensi pada penggunaan bahasa anak, yakni bahasa Melayu ke dalam bahasa Indonesia. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif. Jenis penelitian yang digunakan adalah studi kasus. Teknik pengumpulan data menggunakan teknik observasi, yaitu untuk meninjau berkaitan dengan anak-anak yang sering menonton serial animasi Melayu. lalu menggunakan teknik dokumentansi berkaitan dengan merekam tuturan yang dilakukan, mencatat bentuk penggunaan bahasa Melayu ke dalam bahasa Indonesia yang dituturkan anak. Teknik analisis data menggunakan teknik reduksi data, penyajian data, dan penarikan kesimpulan. Sumber data penelitian ini adalah anak-anak di Desa Sukamanah Kabupaten Sukabumi. Hasil penelitian ini menunjukkan bentuk interferensi bahasa pada bidang linguistik, syakni fonologi, morfologi, dan sintaksis.